A regularization technique for the XFEM: extension to finite deformations, inelastic material behaviour and multifield problems. Issue 1 (October 2016) - Loehnert, Stefan; Beese, Steffen
Abstract: Within the XFEM often near linear dependencies between the standard degrees of freedom and enriched degrees of freedom and also among enriched degrees of freedom occur. During the last years, several remedies to that problem have been presented. Here, an extension of the regularization technique described in [1] to finite deformation problems and inelastic material behaviour as well as to multifield problems is proposed. © 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)